(untitled) (Third Sector Social Economic Review, 2018)
The paper theoretically shaded light on ethical and moral conditions of developing economies of Africa and draw relevant moral lessons from Akhism as an organizational model that used ethics and morals to spur economic development and maintained societal harmony in the later part of Seljuk and Ottoman Empire for close to 710 (1205-1915) years. During that period, a fair distribution of income was achieved, consumers were protected from exploitation and substandard goods and social capital was realized. All as a result of ethical leadership and the Akhism living a moral life style both in public and private. The paper also proposed a unified theoretical frame work for developing ethical and moral decision making process for leaders and managers in both public and private institutions. As a step into achieving moral agency, in order for them to make moral decisions that are critical in the process of transition to democracy and maintenance of social harmony and peace hence economic development of African.